A high-performance asymmetric supercapacitor designed with a three-dimensional interconnected porous carbon framework and sphere-like nickel nitride nanosheets. (25th July 2019) - Peng, Hui; Dai, Xiuwen; Sun, Kanjun; Xie, Xuan; Wang, Fei; Ma, Guofu; Lei, Ziqiang
Abstract : The novel asymmetric supercapacitor was assembled based on a three-dimensional (3D) interconnected porous carbon framework as the negative electrode and 3D sphere-like nickel nitride nanosheets as the positive electrode in aqueous electrolyte. Abstract : To achieve high-energy density of supercapacitors and maintain their intrinsic high power density, the operating voltage should be extended by assembling high specific capacitance electrode materials into an asymmetric supercapacitor (ASC) device. Herein, an ASC was assembled based on a three-dimensional (3D) interconnected porous carbon framework (PRPC-1K) as a negative electrode and 3D sphere-like nickel nitride (Ni3 N) nanosheets as a positive electrode in an aqueous KOH electrolyte. The PRPC-1K was prepared by a simple activation process with biomass poplar root as the carbon precursor, and the Ni3 N nanosheets were successfully synthesized via a simple low-temperature hydrothermal and further urea-assisted nitridation process. Due to the unique structures and high capacitive performances of these materials, the Ni3 N//PRPC-1K ASC assembled based on these two materials achieved the high energy density of 30.9 W h kg −1 at the high power density of 412 W kg −1 and acceptable electrochemical cycling stability with an 81% retention after 5000 cycles.